Comparative Assessment of Global Value Chains' Influence on National Economies - K. S. Goncharova; A. G. Shelomentsev; N. N. Masyuk (Vestnik MGIMO-Universiteta)
In recent decades, a predominant trend in the transformation of national economies worldwide has been the extensive establishment of global value chains and the increased activities of transnational corporations (TNCs). Despite the scale of these phenomena, they have not received adequate scholarly attention, both at the level of individual countries and on a global scale. This paper presents the results of a comprehensive analysis that combines theoretical approaches with empirical investigations of the interplay between the formation and vigorous expansion of global value chains and the dynamics of national economic transformation worldwide. This relationship is examined in the context of foreign multinational corporations operating in sectors such as chemistry and pharmaceuticals, electronics, electrical equipment, and the automotive industry.To achieve the objectives of this study, a range of complementary research methods were employed, including descriptive analysis, comparative analysis, generalization and grouping techniques, and cartographic analysis. The study yields several key findings:Firstly, a global trend of progressive reduction in the share of domestic producers within the industries under consideration has been observed. This trend is most conspicuous in the countries of the former socialist bloc in Central and Eastern Europe, including Poland, Bulgaria, the Czech Republic, Lithuania, Latvia, Estonia, and Romania. These countries previously maintained domestic production levels exceeding 50% of the total volume for the specific product types.Secondly, the field of automobile production exhibits the highest proportion of foreign companies contributing to the total volume of products manufactured. In 33 out of the 58 countries analyzed, foreign multinational corporations account for more than 50% of production. Thirdly, a selection of countries in Western Europe, the Middle East, and the Asia-Pacific region—such as Germany, Italy, France, Israel, the USA, China, Japan, the Russian Federation, India, and Korea—play a substantial role in the development of global value chains through the active expansion of their national TNCs. International companies from these countries are progressively shaping a global socio-economic framework.Lastly, recent years have seen the emergence of a new stage in the evolution of global value chains, prompted by exceptional factors such as the COVID-19 pandemic, the trade conflict between China and the United States, and the conflict in Ukraine. This stage necessitates a profound reconsideration of the strategies employed by current participants in global chains, driven by the imperative of preserving their sustainability.